Historical and Theoretical Framework of the Relation between Higher Education Institutions and the Process of Regional Economic Development - Alexandru Cristian Fotea; Corneliu Gutu (Entrepreneurial Business and Economics Review, 2016)
Objective: The objective is to show how the relation between the higher education institutions and their surrounding environment has evolved over the centuries and how it can increase the economic competitiveness of regional and national economies.